51‐3: 65‐in. Splicing Screen Adapted to a Wide Temperature Range and High Brightness. Issue 1 (28th June 2022) - Wang, Xipeng; Zhang, Wei; Huang, Yinhu; Lim, Byung Cheon; Wang, Zhangtao; Shao, Xibin
Abstract : In this presentation, a TFT‐LCD capable of 2xn splicing is described in detail. The frame of this 65‐inch 4K TFT‐LCD is only 0.9mm, and it can operate normally under hard light and high temperature. After it is spliced into a large screen, the splicing seam is almost invisible at normal viewing distance.